Macroeconomic prospects of the Philippines in 2024-2025: Toward upper middle-income status - John Paolo R. Rivera; Mark Gerald C. Ruiz; Ramona Maria L. Miral (Philippine Institute for Development Studies (PIDS), 2024)
This is the lead chapter of the 2023-2024 Philippine Institute for Development Studies (PIDS) Economic Policy Monitor (EPM). It examines the economic performance of the Philippines for 2023 and at most the third quarter of 2024. It presents conditions driving global, regional, and national outlooks, projections on growth, consumer prices, and prospects coming into 2025 - all of which are relevant to making informed household, enterprise, and policy decisions. As the economy moves towards a better normal, it is challenged by the persistence of headwinds from internal and external factors. As per the Philippine Statistics Authority (PSA), the economy grew by 5.6 percent in 2023 driven by growth in major sectors such as industry and services, while year-to-date headline inflation recorded at 6.0 percent. Like previous EPM publications, this report would likewise include projected growth, and inflation estimates for 2024 and 2025. Considered also are the flow of funds from abroad, employment, financial conditions, use of public funds, and expected consumer and business expectations on the economy's state of health. Taking off from the issues mentioned in previous macroeconomic prospects, this report underscores risks related to inflation, exchange rate movements, fiscal position, and the impact of external factors on national economic growth and development.
Keywords: 330; development; economic prospects; growth; macroeconomic stability; resiliency; upper middle-income status